OBESITY: A CAUSATIVE RISK FACTOR OF BREAST CANCER - Roy, A. S.; Basu, S.; Bandyopadhyay, A. (International Journal of Medicine and Medical Research, 2019)
Background. Obesity, a global health burden and one of the most deleterious diseases have substantially increased prevalence attributable to changing lifestyle of modern times. Persuasive evidence indicates obesity as an independent prognostic factor for developing malignancy in the form of breast cancer particularly in post-menopausal women. Objective. This review aims to focus in comprehensive manner on the biochemical, hormonal and immunological pathways governing the obesity linked breast cancer so that potential treatments may be improvised consequently to provide a cure to this menace, threatening the lives of many. Methods. Literature review of published materials that provide examination of recent or current literature on problem of obesity. Results. Increased body fatness, mainly visceral adiposity may account for predisposing an obese individual to the risk of encountering cancer although the mechanisms for such cancers may vary depending upon the organ affected. Metabolic and biochemical alterations influencing obesity related carcinogenesis, consisting of heightened oxidative stress and bodily inflammation levels with the concomitant rise in pro-inflammatory cytokines are discussed. Pertinent references about elevated levels of serum insulin, insulin-like growth factor, sex steroids and the imbalance in adipokines (adiponectin and leptin) are included as well. Conclusions. Persuasive evidence indicates obesity as an independent prognostic factor for developing malignancy in the form of breast cancer particularly in post-menopausal women. Generation of novel and effective therapeutic interventions for combating the ailment along with positive lifestyle modifications may be improvised consequently to provide a cure to this menace, threatening the lives of many.